Blocking LAIR1 signaling in immune cells inhibits tumor development - Xie, Jingjing; Gui, Xun; Deng, Mi; Chen, Heyu; Chen, Yuanzhi; Liu, Xiaoye; Ku, Zhiqiang; Tan, Lingxiao; Huang, Ryan; He, Yubo; Zhang, Bruce; Lewis, Cheryl; et al. (Frontiers in Immunology, 2022)
The current immune checkpoint blockade therapy has been successful in treating some cancers but not others. New molecular targets and therapeutic approaches of cancer immunology need to be identified. Leukocyte associated immunoglobulin like receptor 1 (LAIR1) is an immune inhibitory receptor expressing on most immune cell types. However, it remains a question whether we can specifically and actively block LAIR1 signaling to activate immune responses for cancer treatment. Here we report the development of specific antagonistic anti-LAIR1 monoclonal antibodies and studied the effects of LAIR1 blockade on the anti-tumor immune functions. The anti-LAIR1 antagonistic antibody stimulated the activities of T cells, natural killer cells, macrophages, and dendritic cells in vitro. The single-cell RNA sequencing analysis of intratumoral immune cells in syngeneic human LAIR1 transgenic mice treated with control or anti-LAIR1 antagonist antibodies indicates that LAIR1 signaling blockade increased the numbers of CD4 memory T cells and inflammatory macrophages, but decreased those of pro-tumor macrophages, regulatory T cells, and plasmacytoid dendritic cells. Importantly, the LAIR1 blockade by the antagonistic antibody inhibited the activity of immunosuppressive myeloid cells and reactivated T cells from cancer patients in vitro and impeded tumor metastasis in a humanized mouse model. Blocking LAIR1 signaling in immune cells represents a promising strategy for development of anti-cancer immunotherapy.